Positioning Male Teachers In the Foundation Phase In South Africa: A Case of One Education District - Nondwe Daphne Mariana Mtshatsha; Bunmi Isaiah Omodan (Faculty of Teacher Training and Education, Universitas Terbuka, 2022)
Observation and literature confirmed that men are unduly scarce in the count of foundation phase teachers in South Africa and the few that are presented as foundation phase teachers are often criticized and ridiculed with the argument that foundation phase teaching is for women. Therefore, the study sought to understand gendered ideologies in order to address the issue of missing male teachers in the foundation phase, which is currently considered to be feminized. Using Sandra Bem’s Gender Schema Theory, the study explores the perceptions embedded within gender issues and how these influence the appointment of male teachers in the foundation phase in the Amathole Education District of the Eastern Cape Province. A qualitative approach was adopted, and a case study research design was employed where six participants (three males and three females) were purposely sampled and interviewed. Data were analyzed using content analyses where some themes emerged. The study revealed that most males are unwilling to work with younger kids, while the study also confirms their roles as very important in the development of younger kids. The study concludes that male teachers’ positive influence cannot be underestimated; hence the government should devise a way to motivate male teacher educators toward the world of work in the foundation phase.